The role of momentum-dark excitons in the elementary optical response of bilayer WSe2 - Jessica Lindlau (Nature Portfolio, 2018)
The electronic band structure of atomically thin transition metal dichalcogenides is strongly sensitive to the number of layers, resulting in modified light emission. Here, the authors investigate the cryogenic emission from bilayer WSe2 to identify the role of momentum-indirect excitons for its optical response.